2013
DOI: 10.1002/bit.24883
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme production by the mixed fungal culture with nano‐shear pretreated biomass and lignocellulose hydrolysis

Abstract: Cellulase, xylanase, and β-glucosidase production was studied on novel nano-shear pretreated corn stover by the mixed fungi culture. The high shear force from a modified Tayor-Couette nano-shear mixing reactor efficiently disintegrated corn stover, resulting in a homogeneous watery mash with particles in much reduced size. Scanning electron microscope study showed visible mini-pores on the fiber cell wall surface, which could improve the accessibility of the pretreated corn stover to microorganisms. Mixed fung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The potential of mixed cultures in biomass degradation has been described for diverse cases and mirrors nature where microbial communities cooperate in degrading plant matter (76,77).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of mixed cultures in biomass degradation has been described for diverse cases and mirrors nature where microbial communities cooperate in degrading plant matter (76,77).…”
Section: Discussionmentioning
confidence: 99%
“…The strains of Aspergillus are known to have high β-glucosidase activity release [19]. Mixed cultures are known to produce enzyme cocktails which are rich in β-glucosidase; thus diminishing the accumulated cellobiose concentration as a result of formation of glucose [20].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that Trichoderma reesei and Aspergillus spp. co-cultures are more effective for maximizing cellulolytic enzyme activities than single cultures by establishing synergistic levels of exocellulases (produced primarily by T. reesei) and endocellulases and β-glucosidases (produced mainly by A. niger) for sustained enzymatic hydrolysis and minimization of product inhibition effects [6][7][8][9]. On the other hand, the C-rich substrate was pre-fermented using Phanerochaete chrysosporium, which has been shown to be effective in delignifying agricultural biomass residues [10,11].…”
Section: Introductionmentioning
confidence: 99%